Implementación de un sistema de gestión de la calidad basado en la NTC 5581 para un programa de educación para el trabajo y el desarrollo humano (2017)
This article refers to the development and implementation of training programs based on the Colombian technical standard 5581 (NTC in Spanish) in an institution of education for work and human development. A diagnosis of the company training program is made as a case study, to understand the degree of compliance with the requirements of NTC 5581. Subsequently, the PDCA cycle to structure the proposal following the logical sequence, including numerals at each stage in the cycle. The planning stage included: environmental analysis, the definition of students’ entry and exit profiles, writing skills and performances, structuring the curriculum, methods of assessment and selection of teaching staff. The doing stage approaches a training methodology and implementation, in which envisages the commitment and involvement of teachers and administrative staff. Then, in the checking stage, control and monitoring methods are exposed. Finally, at the Acting stage sets out strategies for improvement actions based on the analysis of the checking phase.